Phylogeny of Macroptilium (Leguminosae): morphological, biochemical and molecular evidence - Espert, Shirley Mary (2007)
Macroptilium (Benth.) Urban (Phaseoleae, Papilionoideae, Leguminosae) is an American genus of legumes, belonging to subtribe Phaseolinae along with other economically important genera, such as Vigna Savi and Phaseolus L. (the common bean genus). Cladistic analyses based on morphological, biochemical (storage seed proteins) and molecular (nuclear and plastid DNA sequences) data were performed on the 18 species currently ascribed to the genus, exploring several character weighting strategies. Equal weights, implied weighting and different transversion/transition costs were applied. The three data sets were first analyzed with separate partitions, and then combined into a single matrix. This study is the first one to analyze all the species of the genus from a cladistic point of view. In all the most parsimonious trees obtained, Macroptilium is monophyletic with excellent support values. Two monophyletic clades are recovered in almost all the analyses. Both are compound by nine species, and they constitute two sections of Macroptilium. Several interspecific relationships inside the genus are discussed.